Timing of Repeat Cesarean Delivery for Women with a Prior Classical Incision - Ma'ayeh, Marwan; Haight, Paulina; Oliver, Emily A.; Landon, Mark B.; Rood, Kara M. (American Journal of Perinatology, 2020)
Objective This study aimed to compare neonatal outcomes for delivery at 36 weeks compared with 37 weeks in women with prior classical cesarean delivery (CCD).Study Design This was a secondary analysis of the prospective observational cohort of the Eunice Kennedy National Institute for Child and Human Development's Maternal-Fetal Medicine Unit Network Cesarean Registry. Data on cases of repeat cesarean delivery (RCD) in the setting of a prior CCD were abstracted and used for analysis. This study compared outcomes of women who delivered at 360/7 to 366/7 versus 370/7 to 376/7 weeks. The primary outcome was a composite of adverse neonatal outcomes that included neonatal intensive care unit (NICU) admission, respiratory distress syndrome (RDS), transient tachypnea of the newborn (TTN), hypoglycemia, mechanical ventilation, sepsis, length of stay ≥5 days, and neonatal death. A composite of maternal outcomes that included uterine rupture, blood transfusion, general anesthesia, cesarean hysterectomy, venous thromboembolism, maternal sepsis, intensive care unit admission, and surgical complications was also evaluated.Results There were 436 patients included in the analysis. Women who delivered at 36 weeks (n = 176) were compared those who delivered at 37 weeks (n = 260). There were no differences in baseline characteristics. Delivery at 37 weeks was associated with a reduction in composite neonatal morbidity (24 vs. 34%, adjusted odds ratio [aOR] = 0.61 [0.31–0.94]), including a decrease in NICU admission rates (20 vs. 29%, aOR = 0.63 [0.40–0.99]), hospitalization ≥5 days (13 vs. 24%, aOR = 0.48 [0.29–0.8]), and RDS or TTN (9 vs. 19%, aOR = 0.43 [0.24–0.77]). There was no difference in adverse maternal outcomes (7 vs. 7%, aOR = 0.98 [0.46–2.09]).Conclusion Delivery at 37 weeks for women with a history of prior CCD is associated with a decrease in adverse neonatal outcomes, compared with delivery at 36 weeks.Key Points
Keywords: cesarean section; obstetric; repeat; timing; classical; uterine rupture